GAMBARAN SISWA YANG MENGALAMI KECEMASAN MENGHADAPI UJIAN NASIONAL BERBASIS KOMPUTER (UNBK) DI SMP NEGERI 3 PADALARANG - Sugiarto Sugiarto; Heris Hendriana (IKIP Siliwangi, 2020)
The Computer-Based National Examination (UNBK), also called the Computer-Based Test (CBT), is a system of conducting national examinations using computer media that is connected to the internet network. Anxiety students in dealing with UNBK caused by pressure from parents who target high grades, students' disregard in operating computers and the density of learning in schools in preparation for UNBK. Anxiety can cause students to often lose concentration when they work on UNBK training questions held by schools. The purpose of this research is to find out the description or profile of anxiety facing UNBK. The method used in this study is a qualitative method with the type of descriptive research. Data collection techniques used were observation, interviews, and documentation. The results of the study revealed that the two students had an excessive anxiety in facing UNBK, resulting in cold sweat when the lessons were tested, difficulty concentrating so the material given by the teacher was difficult to understand, often permission to go to the toilet to defecate / not have enough energy / helpless, worried, low self-esteem, tense, unable to concentrate, narrowness of the soul, fear, anxiety, lamentation, panic, sleep soundly, threatened, and confusion / dazed and lazy to leave for school. Keywords: Computer Based National Examination (UNBK), Anxiety